Perjanjian Sabdopalon dengan Syekh Subakir dalam Cerita Rakyat Masyarakat Lembah Tidar - Fiqna Nafial Khaq; Sri Prastiti Kusuma Anggraeni (Universitas Veteran Bangun Nusantara, 2025)
This research aims to describe how the agreement between Sabdopalon and Syekh Subakir is represented in the lives of the people of Tidar Valley, Magelang. The focus of this research is to reveal the content of the agreement, the process of spiritual negotiation that lasted for 40 days and 40 nights, and to analyze the moral messages, values and norms contained in the agreement. The research method used is a qualitative-descriptive approach with data collection techniques through in-depth interviews with the caretaker of Gunung Tidar and community leaders, as well as document and literature reviews. The study results show that this agreement symbolizes cultural acculturation between Islamic teachings and Javanese traditions. The agreement includes several key conditions: the spread of Islam must be conducted peacefully without coercion, Javanese traditions and customs must be respected, Islamic places of worship must reflect local culture, and Islamic teachings must be adapted to local wisdom. The Sa Monument at the summit of Gunung Tidar serves as a physical symbol of this agreement, with the meaning